Collaborative Transformation: The Effect Of Co-Creation, Marketing Strategy, And Financial Management On Business Value And Competitiveness Of Smes In Garut Regency - Yusuf Tojiri (UNIVERSITAS PAKUAN, 2025)
The level of competitiveness and sustainability of Small and Medium Enterprises (SMEs) in the digital era requires strategies that are not only innovative but also integrated. This study aims to analyze the effect of co-creation, marketing, and financial management on SMEs' business value and competitiveness in the Garut Regency. This study uses a quantitative approach with a causal associative research type. The study population was all SMEs registered at the Garut Regency Cooperative and MSME Office, with a sample of 80 respondents determined through purposive sampling. Data were collected through a closed Likert scale questionnaire and analyzed using validity, reliability, multiple linear regression, and classical assumption tests. The results showed that co-creation strategy, marketing strategy, and financial management significantly positively influence both partially and simultaneously on increasing SMEs' business value and competitiveness. Customer involvement in innovation, implementation of digital marketing, and sound financial governance proved to be essential foundations in building SMEs' competitive advantage. The findings provide theoretical implications for developing collaboration and digitalization-based competitiveness models and practical implications for SMEs and the government in designing more focused and sustainable development strategies